Unenforceable Target Movable Property Under Enforcement (Journal of Legal Studies, 2021)
Nowadays, enforcement is one of the crucial elements of justice. Right to the property is guaranteed by the constitution and therefore exercising property rights is one of the key goals of justice, the latter is implemented through effective and efficient enforcement.The present study is mainly dedicated to the specifics of enforcing property rights. Methods used in the research involve qualitative study, the latter encompasses observation of rules and regulations in national and international practices based on primary and secondary legal and historical sources, including official legal documents, court decisions as first-hand material, as well as derived sources such as various articles, monographs, comments on laws and regulations, etc. The comparative method used in the study is aimed at demonstrating differences and similarities of enforcement rules and procedures in different legal systems, revealing their advantages and disadvantages, while practical examples focus on the identification of gaps to lay the path for better legal solutions. The complex scrutiny of the subject to the present research allows to review it from different angles and suggest legal recommendations to raise the efficiency of the enforcement system and subsequently provide a firm basis for justice.